MANTLE-DERIVED REDUCED FLUIDS: RELATIONSHIP TO THE CHEMICAL DIFFERENTIATION OF PLANETARY MATTER - Kadik A.A. (My University, 2003)
The application of phase equilibrium methods to the estimation of oxygen fugacity (fO2) showed that the present-day lithospheric and asthenospheric upper mantle layers are moderately oxidized. Their fO 2 values fall above the stability field of metallic iron. The activities of Fe3+ components of upper mantle minerals indicate fO2 conditions, under which CO2 and H2O are prevalent in deep fluids and carbonates are stable. Some peridotites of the Archean lithosphere and the asthenospheric and lithospheric mantle of rift zones axe reduced, which suggests that fluids with high CH4 concentrations, as well as fluids with widely varying concentrations of CH4, H 2, CO2, and H2O, can also occur in the upper mantle. The peridotites with very low fO2 values are considered as mantle rocks retaining fO2 values characteristics of early stages of the Earth's evolution. Low fO 2 values in some lithospheric zones can be explained by mass exchange with deep reduced zones of the upper mantle. The heterogeneous accretion of the Earth, evolution of the metallic core, and large-scale melting (formation of a magma ocean) were probably responsible for the early significant fO2 increase in the upper mantle. Oxygen redistribution and related fO2 changes in the Earth's interior have occurred during the prolonged subsequent chemical differentiation of the planet, and they were probably connected with the evolution of the metallic core, deep degassing, magma generation, subduction processes, and upwelling of mantle plumes and asthenospheric diapirs. Geochemical data show that lithospheric subduction is the principal mechanism responsible for the increase in mantle oxygen fugacity in this period. Hence, an increase in mantle fO2 is caused by H2O, CO2, and Fe3+ flows related to the subduction of oxidized lithospheric plates.